Validity of Project-Based Electronic Worksheets to Improve Students' Critical Thinking Ability - Ilana, Nadia; Cintamulya, Imas (Bioedukasi: Jurnal Pendidikan Biologi, 2022)
Project-Based Learning is one of the learning approaches that can improve students' critical thinking skills. The aims of this study are to 1) design a Project-based e-worksheet in Biology to improve students' critical thinking skills, and 2) describe a Project-based e-worksheet in Biology to improve students' critical thinking skills. The model used in this study is a 4-D development model which has 4 stages, namely: 1) the definition stage, 2) the design stage, 3) the development stage, and 4) the disseminate stage. However, this research only reached the development stage, namely the expert validation stage due to limitations in the study. Validity assessment criteria include the appropriateness of content, systematics, graphics, and language. The data on the validity of the e-worksheet were obtained from the results of the assessments of three expert validators, namely one biologist and two biology subject teachers. The results showed that the average obtained in the aspect of content feasibility was 79.6%, systematic feasibility was 88.1%, graphic feasibility was 98.3%, and language feasibility was 83.3%. The overall average percentage of Project-based e-worksheets on Biology subjects to improve students' critical thinking skills is 87.3%. with very valid categories based on the eligibility criteria of content, systematics, graphics, and language. because the percentage score is above 70%. Thus, it can be concluded that the Project-based e-worksheet on Biology subjects to improve students' critical thinking skills has been designed to meet the validity criteria